Probing the interactions of GlcNH2 with boric acid via NMR spectroscopy. Issue 29 (20th July 2021) - Jia, Lingyu; Liu, Rui; Lv, Jiayu; Liu, Luqi; Zhang, Zhenzhou; Wang, Yingxiong; Hou, Xianglin
Abstract : A 1 : 1 chelate boron complex coordinated at cis -1, 2 positions of GlcNH2 was identified as the major species via 1 H and 13 C INEPT DOSY NMR spectroscopy, 1 H– 15 N HSQC spectra, and spin–lattice relaxation times ( T 1 ) of the 13 C1 nucleus. Abstract : The essential role of boronic esters in controlling both the direction and selectivity of chemical reactions as well as their significant function in catalytic activity have been demonstrated for industrially important processes. The specific interaction analyses of the monosaccharide GlcNH2 with boric acid are of interest since monosaccharides serve as model systems for the more sophisticated carbohydrate molecules. The interaction of GlcNH2 with boric acid was systematically investigated by numerous NMR techniques. A 1 : 1 chelate boron complex coordinated at the cis -1, 2 position of GlcNH2 was identified as the major species in DMSO-d6 solution via 1 H and 13 C INEPT DOSY NMR spectroscopy. This specific boron nitrogen coordination mechanism was further supported by the 1 H– 15 N HSQC spectra. Variations in the spin–lattice relaxation times ( T 1 ) of the 13 C1 nucleus also provided quantitative data regarding this non-covalent interactions. This is an application of 1 H, 13 C INEPT DOSY, 1 H– 15 N HSQC, and relaxation methods to study such aggregations in solutions. These methods have potential applications in the characterization of reactive intermediates in biomass conversions.